ANALISIS PERBEDAAN KINERJA KEUANGAN ANTARA BPD SYARIAH DAN BPD KONVENSIONAL DI JAWA MENGGUNAKAN METODE RGEC - Novrina Atika Putri; Siti Zulaikha (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The RGEC approach is an assessment of the latest bank soundness that consists of risk profile, good corporate governance, earnings, capital, each of which is projected with the bank's financial performance. RGEC is able to identify problems early, solve problems more quickly, and implement better GCG and risk management so that it is resistant to crisis. This study aims to analyze whether there are differences between the level of health of conventional BPD and Islamic BPD in Java using the RGEC approach. This type of research is quantitative research. The sample in this study was selected by means of purposive sampling, based on predetermined criteria then obtained 4 conventional BPDs and 4 Islamic BPDs. The data analysis technique used in this study is the two different test averages (independent sample t-test). The results of this study prove that there are significant differences in the FDR and ROA variables between conventional BPD and Islamic BPD and there are no significant differences in the NPF, GCG, CAR variables.Keywords: RGEC, Bank Healthy, NPF, FDR, GCG, ROA, CARREFFERENCESDaniswara, Fitria dan Nurmadi. 2016. Analisis Perbandingan Kinerja Keuangan Berdasarkan RGEC pada BUK dan BUS periode 2011-2014. GEMA, THN XXX/51/Februari-Juli 2016.Kasmir. 2012. Analisis Laporan Keuangan. Jakarta: PT. Bumi Aksara.Kasmir. 2012. Dasar-dasar Perbankan. Edisis Revisi. Jakarta: PT. Grafindo Persada.Kasmir. 2012. Manajemen Perbankan. Edisi Revisi II. Jakarta: Rajawali Pers.Marwanto. 2011. Analisis Komparatif Tingkat Kesehatan Bank Umum Syariah dan Bank Umum Konvensional dengan Metode RGEC periode 2012-2013. Jurnal Ekonomi.Otoritas Jasa Keuagan No.10/SEOJK. 03/2014. Tentang Faktor PenilaianSelf Assessment GCG BUS/UUS-(www.ojk.go.id). Diakses tanggal 13 Mei 2019.Rifai. 2008. Islamic Financial Management. Jakarta: PT. Raja Grafindo Persada.Siregar, Sofyan. 2015. Metode Penelitian Kuantitatif: Dilengkapi Perbandingan Perhitungan Manual & SPSS. Jakarta: Kencana.Sugari. 2015. Analisis Perbandingan Tingkat Kesehatan Bank Syariah dan Konvensional dengan menggunakan Metode RGEC. Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman.Sugiono. 2007. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta.Sulistianingsih, H & Maivalinda. 2018. Analisis Perbandingan Tingkat Kesehatan Bank Konvensional dan